Ethik als Vermittlung zwischen Generationen in den Pastoralbriefen - POPA, Romeo (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
In the Pastoral Letters the problem of the relationship between age groups is most clearly expressed in early Christian literature. In the course of the reorganization of church structures resistance against younger leaders is attested (1Tim 4:12-15). New “false doctrines” further fuel the tension between generations because especially “young widows” (1Tim 5:11-15; 2Tim 3,6) show interest in such theological offers. Consequently, they are also given special attention in the paraenesis, whereby the paternalistic tendencies are radicalized. The theological confrontation with the opponents and the development of age-appropriate ethic discourses are illuminated on the background of the relations between generations.